PENGELOLAAN MUSYAWARAH GURU MATA PELAJARAN BIOLOGI DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI KOTA BANDA ACEH - Era Irhamni; Murniati .; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The management of MGMP (teacher discussion group) in improving teacher professionalism is aligned with the management principles by optimizing the available resources. This study is aim to find out the management of MGMP Biology’s teachers in Banda Aceh to develop teacher competence. This study applied qualitative method by using interview, observation and documentation as data gathering technique. The participants were the MGMP committee, the members and the headmasters. The result showed that (1) strategy in planning the MGMP program was done by determining the aim of the program, forming the organization structure in form of commitee, determining and delegating job allocation, cordination through social media and involving relevant party internally, (2) MGMP program conducted once a month around two hours at senior high school in Banda Aceh, (3) controlling of program was done internally by head of MGMP, school supervisor, and headmaster through direct visit, (4) while Lack of staff ability, time constraints in managing the MGMP, and the absence of self-evaluation for staff performance and program evaluation were the drawbacks in the management of MGMP Biology’s teachers. However, the MGMP of Biology’s teacher has succeeded in conducting some programs effectively which able to improve teacher professional competence. Keyword: management, MGMP, professional competence